Tourism in Qatar: Pathway Toward a Place-Based Ecotourism Policy and Sustainable Practices - Chatziefthimiou, A. D.; Weber, A. S.; Hinnawi, R.; Petrovska, I.; Baeuerle, M. (Springer Nature Switzerland, 2026)
Ecotourism and Sustainable Tourism have become standard practices in international tourism development strategies, officially endorsed by such organizations as the United Nations World Tourism Organization (UNWTO) and The International Union for Conservation of Nature (IUCN). However, very few countries have succeeded in re-organizing their tourism industries for long-term sustainability. Qatar is fortunate to possess a relatively new tourism industry such that sustainable practices can be built from the ground up. However, Qatar’s natural environment experiences both high natural stressors (water scarcity, high temperatures, low productivity and fragile ecosystems, etc.) as well as unique anthropogenic stressors (rapid urbanization, high CO2 emissions, terrestrial and marine habitat loss, coastal dredging, etc.). Therefore, incorporating sustainable tourist principles into all dimensions of tourism development is imperative to prevent serious long-term negative environmental, economic, social, and cultural impacts for the State of Qatar. This chapter outlines the challenges facing tourism development in Qatar, showcases the discreet steps to transition tourism operations in nature toward ecotourism, and offers suggested best practices as well as a regulatory framework for sustainability in this sector.